2007
DOI: 10.1111/j.1440-172x.2007.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Reflective practice in nursing care: Embedded assumptions in qualitative studies

Abstract: Qualitative nursing researchers have long recognized that reflective practice (RP) seems to be a valuable tool in nursing care. The aim of the present meta-study was to analyse current qualitative research on RP in nursing care, in order to create and synthesize the knowledge and the understanding of registered nurses' RP. Using a meta-study synthesis approach, embedded assumptions were identified in qualitative studies that have influenced the way researchers have interpreted and made sense of RP in nursing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 77 publications
(315 reference statements)
0
36
0
3
Order By: Relevance
“…Critical reflective practice (or reflective practice), although ambiguous to define, is identified as both an internal and external process (Durgahee, 1998;Gustafsson, et al, 2007;Ruth-Sahd, 2003 (Crandall & Getchell-Reiter, 1993), challenges to the status quo and institutional power happen and nurses move away from routines to a state of mental arousal and intellectual curiosity (Durgahee, 1996), increases in clinical reasoning and intrinsically motivated learning develop (Murphy, 2004), academic self-concept is enhanced (e.g., a determination to continue with education) (Mountford & Rogers, 1996), increases in confidence and ability to provide the rationale for patient care are demonstrated (McCaugherty, 1991), intentions to engage learned strategies in future, similar care situations are exhibited (Briggs, 1995), an ability to integrate theoretical concepts to practice occurs (Ruth-Sahd, 2003) and specific changes to practice develop (Paget, 2001). In only one study was it identified that reflection had no statistically significant effect on a learning outcome (Low & Kerr, 1998).…”
Section: Relationship Between Critical Reflective Practice and Work Ementioning
confidence: 99%
See 1 more Smart Citation
“…Critical reflective practice (or reflective practice), although ambiguous to define, is identified as both an internal and external process (Durgahee, 1998;Gustafsson, et al, 2007;Ruth-Sahd, 2003 (Crandall & Getchell-Reiter, 1993), challenges to the status quo and institutional power happen and nurses move away from routines to a state of mental arousal and intellectual curiosity (Durgahee, 1996), increases in clinical reasoning and intrinsically motivated learning develop (Murphy, 2004), academic self-concept is enhanced (e.g., a determination to continue with education) (Mountford & Rogers, 1996), increases in confidence and ability to provide the rationale for patient care are demonstrated (McCaugherty, 1991), intentions to engage learned strategies in future, similar care situations are exhibited (Briggs, 1995), an ability to integrate theoretical concepts to practice occurs (Ruth-Sahd, 2003) and specific changes to practice develop (Paget, 2001). In only one study was it identified that reflection had no statistically significant effect on a learning outcome (Low & Kerr, 1998).…”
Section: Relationship Between Critical Reflective Practice and Work Ementioning
confidence: 99%
“…Qualitative research, primarily completed with nursing students, has identified that both internal and external resources, resources representative of critical reflective practice (Gustafsson, et al, 2007;Ruth-Sahd, 2003), can be implemented within learning and work environments to reduce moral distress, which may also enhance work engagement.…”
Section: Literature Synthesismentioning
confidence: 99%
“…Selon Gustafsson, Asp, et Fagerberg (2007), les concepts de réflexivité, de pratique réflexive, de pensée critique et de processus réflexif sont utilisés comme des synonymes dans la littérature scientifique. Malgré l'absence de consensus quant à la définition de la pratique réflexive (Atkins et Murphy, 1993), des auteurs s'entendent pour dire qu'elle permet de soutenir l'analyse critique des connaissances et de l'expérience afin de favoriser la compréhension d'une situation donnée (Mann, Gordon, et MacLeod, 2009).…”
Section: Pratique Réflexiveunclassified
“…Continuing professional development is essential for nursing practice and the Irish Nursing Board (An Bord Altranais, 2000a) proposes reflective practice as a mode of accomplishing this. It facilitates an opportunity for nurses to reflect on essential nursing care and how it benefits the patient (Gustafsson et al, 2007). Reflection may help develop higher order cognitive skills, which helps reduce the theory/practice gap and encourages nurses to become critical thinkers (Burton, 2000).…”
Section: Introductionmentioning
confidence: 99%